State and problems of physical education in regional general education educational institutions - Margarita Mameshina; Irina Maslyak; Vjacheslav Zhuk (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to study a state and problems of physical education in regional general education educational institutions. Material and Methods: 29 teachers of physical culture of Izyum and Izyum district of the Kharkov region took part in the research. The following methods were used: theoretical analysis and generalization of scientific literature, opinion poll, and mathematical statistics. Results: it is established that most of teachers aren't absolutely satisfied with the relation of pupils to the process of physical education; they are inclined to carrying out separate classes on a sexual sign; estimate health and the level of physical fitness of pupils as "average"; consider that it is necessary to control the development of motive abilities and point to an acute shortage of computer databases. It is defined that there isn't out-of-class work on physical education (perhaps due to the lack of financing) in the third part of regional general education educational institutions. Conclusions: it is established that the main problems of physical education in regional general education educational institutions are an acute shortage of financing and an insufficient material base.